Featured Cover. Issue 12 (26th November 2021) - Aryanfar, Amin; Gholami, Aslan; Pourgholi, Mahdi; Zandi, Majid
Abstract : The cover image is based on the Original Article Multi‐Criteria Wind Potential Assessment Using Fuzzy Logic in Decision‐Making: A Case Study of Iran by Amin Aryanfar, Mahdi Pourgholi et al., https://doi.org/10.1002/we.2640 .